1970
DOI: 10.1098/rspa.1970.0157
|View full text |Cite
|
Sign up to set email alerts
|

An electron microscope study of evaporating small particles: the Kelvin equation for liquid lead and the mean surface energy of solid silver

Abstract: An electron microscope study of evaporating liquid lead particles, formed on carbon substrates by nucleation from the vapour, has led to a confirmation of the Kelvin equation which relates equilibrium vapour pressure to surface curvature. Observations of the same kind made on particles of evaporating solid silver have produced evaporation curves similar to those for lead. Interpretation of these curves in terms of the Kelvin equation for solids has yielded a value for the mean surface energy of silver of 1.20 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

1972
1972
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…A similar phenomenon (i.e., sublimation) of silver was reported by Sambles et al 34 years ago [15]. They conducted a conventional, not a high resolution, electron microscopy study of evaporating small silver particles supported on an amorphous carbon substrate.…”
mentioning
confidence: 65%
“…A similar phenomenon (i.e., sublimation) of silver was reported by Sambles et al 34 years ago [15]. They conducted a conventional, not a high resolution, electron microscopy study of evaporating small silver particles supported on an amorphous carbon substrate.…”
mentioning
confidence: 65%
“…2 that, more locally, for specific atom's moves we can use energy-scale Boltzmann factors. However, it is instructive to consider simple equilibrium approaches, 47 supplemented with additional assumptions on the particle geometry, which yield useful phenomenological results.…”
Section: Phenomenological Thermodynamic Model For Sublimationmentioning
confidence: 99%
“…47 Assuming a spherical (or an on-surface hemispherical) "drop" model for the NP, with radius r, one can employ the Kelvin equation for evaluating the partial pressure, P r , in the gas phase adjacent to the NP surface:…”
Section: Phenomenological Thermodynamic Model For Sublimationmentioning
confidence: 99%
“…(2) Sublimation becomes dominant at the temperature higher than ∼600 °C. It was reported that sublimation temperature decreases with the decreasing particle size, which follows kinetics of sublimation of nanoparticles . Asoro et al confirmed the correlation between sublimation temperature and particle size by observing silver nanoparticles via in situ heating TEM analysis .…”
Section: Results and Discussionmentioning
confidence: 91%